Plasma steroid profiles and ovarian response in llamas treated with eCG for superovulation combined with exogenous progesterone during early luteal phase - Aller Atucha, Juan Florencio (2019)
The objective of this study was to evaluate the effects of plasma progesterone (P4) concentrations during eCG-ovarian follicular superstimulatory treatment performed in early luteal phase and estradiol concentrations during peri-ovulatory period on ovarian response, number and embryo quality. On Day -2, females (n = 75) having a follicle ≥7 mm were treated with GnRH to induce ovulation. On Day 0, females that had ovulations (n = 54) were treated with 1000 IU eCG and were assigned to one of two treatments: (1) intravaginal device (ID) containing 0.5 g P4 (P4 group) and (2) no ID (Control group). On Day 5, females were administered PGF2α and the ID was removed. On Day 7 and 8, females were mated and embryo recovery was performed 7 or 8 days later. Blood samples were collected from Day 0 to 9. Number (± SD) of follicles ≥7 mm on day of mating was greater (P =  0.04) in the control (9.7 ± 4.2) than P4-treated (6.7 ± 4.9) group; number of corpora lutea did not differ (5.5 ± 3.1 and 5.2 ± 3.4 respectively). Ovulation rate was greater (P <  0.01) in the P4-group (77.4%; 130/168) than control group (53.3%; 135/253). Number of embryos with an excellent grade (grade 1) tended to be greater (P =  0.07) in the P4-group (82.4%; 42/51) than control group (65.4%; 36/55). It was concluded that supplementation with exogenous P4 during eCG treatment in early luteal phase inhibits excessive follicular growth, increases ovulation rate and improves embryo quality.